SOCIAL PSYCHOLOGICAL CHARACTERISTICS OF ADOLESCENT BEHAVIORAL DEVIATIONS (Academicia Globe: Inderscience Research, 2022)
It is said that today's teenagers have some physical, mental and political advantages over their predecessors. They are expected to show earlier sexual maturation, socialization, and mental growth. The transition from adolescence to adolescence usually begins in the 5th grade. This period is explained by the concept of transition.